Spatial deformation estimation and long term structural health monitoring in underground engineering - Sham, Wai Lun (2012)
The current understanding of geotechnical engineering and the development of underground structural health monitoring (SHM) methodology are still far behind the pace of the underground infrastructure development. The detection and estimation of time dependent displacement in tunnels and caverns have always been in the top priority to research in the underground engineering sectors. It is important to resolve the black box for both long term and short term time-dependent deformation in tunnels to provide estimates for support installation time, design consideration and possible collapse detection. This thesis aims to initiate solutions to estimate and monitor the time dependent deformation in underground infrastructures. It begins with a detail summary of the factors that influence the time dependent deformation and the traditional SHM techniques in underground engineering. This is followed by the development of a new excavation advancement rate incorporated longitudinal displacement profile (ARLDP) to address the short term time-dependent displacement in tunnel caused by the excavation activities. The complementary introduction of the superimposed longitudinal displacement profile (SLDP) mapping technique utilizes onsite convergence measurement to provide quick and reliable estimates of the tunnel displacement profile. The highlight of this thesis comes from the initiation development of the real-time long-term spatial SHM for underground engineering. The development starts with describing the SHM system layout and investigating its feasibility of using the Brillouin Optical Time Domain Reflectometry (BOTDR) fiber optic sensing technique in underground engineering. A geometrical analysis is performed aiming to transform the strain measurement acquired from the BOTDR sensors to displacement data. The major challenges in this research are found in the calibration of the BOTDR strain sensor and the investigation of the BOTDR fiber optic sensor (FOS) installation method. Through series of experimental studies, the author has successfully addressed the technical and physical deficiency in employing the BOTDR FOS to develop the underground spatial SHM system. An onsite demonstration is also presented in this thesis to prove the feasibility and the possibility to develop such real-time long-term spatial SHM system for underground engineering. It is hope that this research would make a significant contribution and valuable reference for future development in underground engineering.